1986
DOI: 10.1046/j.1537-2995.1986.26286152900.x
|View full text |Cite
|
Sign up to set email alerts
|

Platelet storage for 7 days in second‐generation blood bags

Abstract: Plastic storage bags designed to optimize O2 and CO2 transfer to preserve platelets for 7 days prior to transfusion were studied in vivo and in vitro. Platelets stored 7 days in second-generation CLX bags were compared to platelets stored 3 days in standard (CL-3861) 3-day storage bags and platelets transfused within 24 hours of collection. The CLX bags maintained concentrate pH at a mean of 6.85 +/- 0.03 (SEM) after 7 days, while in standard bags after 3 days of storage, the mean pH was 6.46 +/- 0.03. A small… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
1

Year Published

1987
1987
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(63 citation statements)
references
References 13 publications
4
58
1
Order By: Relevance
“…While we do not believe there is a meaningful effect from this variable, we cannot conclusively demonstrate that from the data presented here. However, previous studies have indicated that both the Miles CLX bags and Cobe Spectra’s ELP PVC bags are favorable for the extended storage of platelets [40, 41, 42, 43, 44]. …”
Section: Discussionmentioning
confidence: 99%
“…While we do not believe there is a meaningful effect from this variable, we cannot conclusively demonstrate that from the data presented here. However, previous studies have indicated that both the Miles CLX bags and Cobe Spectra’s ELP PVC bags are favorable for the extended storage of platelets [40, 41, 42, 43, 44]. …”
Section: Discussionmentioning
confidence: 99%
“…Longer platelet storage times have been reported to decrease posttransfusion platelet viability. [20][21][22][23] However, some investigators have suggested that storage adversely affects only platelet concentrates rather than apheresis platelets. 24 In our study, an equal benefit of platelets stored for 48 hours or less was seen for all the types of platelets transfused.…”
Section: Org Frommentioning
confidence: 99%
“…This combination of storage container, agitation, preservative solution, temperature, and the use of approximately 50 mL of plasma permits satisfactory preservation of platelets for up to 7 days 23,24 However, several instances of bacterial contamination of PCs stored for this period have been reported 25,26 and the storage time from collection to transfusion is is now limited to 5 days. 27 Because several units of PC are pooled to obtain a dose for one transfusion, one reason to use single-donor apheresis platelets is to minimize the number of donors to which the patient is exposed and, theoretically, to minimize the likelihood of disease transmission.…”
Section: Prophylactic Platelet Transfusionsmentioning
confidence: 99%